SOSIALISASI RANCANGAN UNDANG-UNDANG PASAL 485 PADA PENANGGULANGAN CYBER SEX - Yusnani Yusman; Magfirah Magfirah (JCH (Jurnal Cendekia Hukum), 2018)
The violation of the law is: "Article 32, which reads every person who played, display, use, possess or store pornographic products as referred to in Article 6 shall be liable to a maximum imprisonment of 4 (four) years and / or a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah). (Note: Article 6 of each person is prohibited from playing, displaying, exploiting, memorizing or storing pornographic products as referred to in Article 4 paragraph (1), except those authorized by law". Islamic law views any extramarital sexual relations as adultery and threatening with punishment, whether the perpetrator is married or not, done likes it or not. Our source of law Qs, 24: 2: "The woman who commits adultery and the adulterer then hail every one of them a hundred times dera. This uses the method of empirical normative legal research, which is "Explaining what it is about a legal event or legal conditions. The municipal or local government seems impressed still in determining the termination of access to pornography or cybersex including socialization of positive criminal law about the crime of single adultery such as Draft Law Article 485. And the proposed criminal law of 2 years imprisonment or fine penalty of R 50,000,000.00 (Fifty million rupiahs) for a single individual. As the law of takzir.